The voyage of the Dawn Treader - Lewis, C. S. (Clive Staples), 1898-1963.; Baynes, Pauline (New York : HarperCollins, 1994)
Lucy and Edmund, accompanied by their peevish cousin Eustace, sail to the land of Narnia where Eustace is temporarily transformed into a green dragon because of his selfish behavior and skepticism.
English language and literature.
Keywords: Fantasy -- fiction; Children's stories; Narnia (Imaginary place) Juvenile -- fiction; Narnia (Lieu imaginaire) Romans, nouvelles, etc